A Randomized Study Comparing Levofloxacin, Omeprazole, Nitazoxanide, and Doxycycline versus Triple Therapy for the Eradication of Helicobacter pylori - Basu, P Patrick (Nature Publishing Group, 2011)
OBJECTIVES: Resistance to standard Helicobacter pylori (HP) treatment regimens has led to unsatisfactory cure rates in HP-infected patients. This study was designed to evaluate a novel four-drug regimen (three antibiotics and a proton pump inhibitor (PPI)) for eradication of HP infection in treatment-naive patients. METHODS: Patients with a diagnosis of HP gastritis or peptic ulcer disease confirmed using endoscopy and stool antigen testing were eligible for inclusion in this study. All patients underwent a washout period of 6 weeks from any prior antibiotic or PPI usage. Patients were then randomized to either levofloxacin, omeprazole, nitazoxanide, and doxycycline (LOAD) therapy for 7 days (LOAD-7) or 10 days (LOAD-10), including levofloxacin 250 mg with breakfast, omeprazole 40 mg before breakfast, nitazoxanide (Alina) 500 mg twice daily with meals and doxycycline 100 mg at dinner, or lansoprozole, amoxicillin, and clarithromycin (LAC) therapy for 10 days, which included lansoprozole 30 mg, amoxicillin 1 g with breakfast and dinner, and clarithromycin 500 mg with breakfast and dinner. HP eradication was confirmed by stool antigen testing at least 4 weeks after cessation of therapy. RESULTS: Intention-to-treat analysis revealed significant differences (P<0.05) in the respective eradication rates of the LOAD therapies (88.9% (80/90) LOAD-10, 90% (81/90) LOAD-7, 89.4% (161/180) for combined LOAD) compared with those receiving LAC, 73.3% (66/90). There were no differences in adverse effects between the groups. CONCLUSIONS: This open-label, prospective trial demonstrates that LOAD is a highly active regimen for the treatment of HP in treatment-naive patients. A large randomized controlled trial is warranted to further evaluate the efficacy of this regimen.